Automating scenario analysis of human and system reliability - Sutcliffe, Alistair G.; Gregoriades, Andreas (My University, 2007)
The system reliability analyzer tool for analyzing the reliability of system designs is described and its use illustrated in a system engineering case study of a naval command and control system. The performance of systems consisting of human operators and technology components is assessed by Bayesian nets, which calculate error probabilities from inputs of agent properties and environmental conditions. The tool tests scenarios representing the system design and its operational behavior, which is modeled as cycles of command and control tasks. The tool indicates weak points in the scenario sequence and assesses the reliability of one or more system designs with a set of operational scenarios and a variety of environmental conditions.
Keywords: Human factors; System reliability; System requirements and specifications